Regularity and robustness in monotone Bayesian games - Beggs, A (Elsevier, 2015)
This paper defines regular and weakly regular equilibria for monotone Bayesian games with one-dimensional actions and types. It analyzes the robustness of equilibria with respect to perturbations. It also proves an index theorem and provides applications to uniqueness of equilibrium.